Does education improve employee benefits in Vietnam? The first evidence from matched employer–employee data - Tran Trung; Nguyen Tien-Trung; Trinh Thi Phuong Thao; Le Thi Thu Hien (Cogent Education, 2019)
Based on a uniquely matched firm-worker panel dataset for 2013 and 2015, this study is the first to consider the effect of education on employee benefits in terms of wages and quality of employment. We find that only college or university education has a positive influence on employee wages when taking into account worker characteristics alone but the wage premium declines when both firm and worker characteristics, as well as time-invariant unobservable factors, are controlled for. While there are many studies on the wage premium of education, the role of education on the quality of employment remains largely unexplored. Our results show that in fact, only college or university graduates benefit from a statistically significant difference in the quality of employment in comparison with their colleagues without such education. The findings suggest that higher education programs play an important role in employee benefits.